EFFORTS TO EMPOWER MSMES IN PANCI VILLAGE IN INCREASING FAMILY INCOME (Study on MSMEs in Panci Village in Porong District, Sidoarja Regency) - Enny Istanti; RM Bramastyo KN; Achmad Daeng GS (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Economic development is generally carried out by developing countries aimed at creating economic development that can be enjoyed by the community. Method usedi.e. qualitative allows data analysis to be carried out when researchers are in the field or after returning from the field a new analysis is carried out. Research result : 1. Efforts to empower village SMEs Pan in increasing family income in a way technology utilization, making packaging more attractive, empowerment programs regarding facilities and infrastructure and the role of the Government in increasing the marketing of MSME products, 2. Efforts for MSMEs in Kampung Panci to increase family income by increasing family income and making residents more productive and creative, 3. The Role of the District on Village SMEs Pan. Conclusionhave not used online media as marketing access; lack of facilities and infrastructure, can increase income and the absence of assistance provided by the District against unequal to all business actors in MSMEs.